Abbreviation and Acronymy in English Arabic Translation - al-Qinai, Jamal (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThe use of abbreviations and acronyms is a relatively rare and inconsistent phenomenon in Arabic morphology. Ancient Arab philologists as well as those of late preferred using words in their entirety. This practice is consistent with the somewhat reserved formation of blends and abbreviated forms in Arabic morphology. While native acronyms are still rare in modern Arabic, the presence of abbreviated forms is by and large the outcome of loan-buzz words or transliterated foreign forms. Despite the rarity of acronyms in ancient and modern Arabic texts, these abbreviations represent no small challenge to the Arabic-English translator who is concerned with issues of equivalence and similarity. To better understand the provenance and dissemination of such forms we can point to several linguistic and sociolinguistic factors that will maximize the similarity between source and target text.